Mapping Essential Podcasting Competencies for Micro-Credential Development in Higher Education: An Exploratory Factor Analysis - Laksmi Dewi; Ahmad Fajar Fadlillah; Della Amelia (Universitas Pendidikan Ganesha, 2026)
The number of podcasters and podcast listeners continues to increase each year, including among university students. Many individuals are interested in becoming podcasters; however, they often face challenges in understanding the necessary skills and how to start podcasting. This study examines the competency needs required to develop the micro-credential program ‘How to be a Podcaster,’ with the aim of mapping more targeted competencies as the program's curriculum objectives. Competency mapping in this study is the initial step in the overall development of the micro-credential program. The study involved 131 samples selected using simple random sampling techniques. The samples consisted of first to third-year students who were interested in becoming content creators. Data were collected using a structured questionnaire distributed through an online survey via the Google Forms platform. The data were analyzed using structured factor analysis, involving Exploratory Factor Analysis (EFA), Eigenvalue analysis, and Varimax rotation to identify patterns and trends in competency needs. The analysis revealed 11 sub-competencies that are the main targets of the program. These eleven sub-competencies are derived from three core competencies essential for basic podcasting skills: communication skills, audio production, and content management. These findings provide a foundation for developing a micro-credential program that can holistically meet the competency needs of aspiring podcasters. Each sub-competency is further elaborated in the discussion section.